The contribution of clay minerals in the landslides occurrence within Pindos flysh formation - Vacondios, I.; Konstantopoulou, G.; Karadassi, St. (Bulletin of the Geological Society of Greece, 2007)
An engineering geological investigation of the "Potamouli" area located west of Grevena town, for a water dam foundation, has revealed some geotechnical problems related to landslide phenomena. Landslides are of limited extent in the reservoir area, but significant instabilities were identified within the broad catchment basin. The basin is built up mainly by the chaotic unit of Pindos flysch formation, which consists of a silty clayey matrix with heterogeneous inclusions of rock masses in diverse frequency and size. In order to investigate the major contributing factors to landslide occurrence, several physical properties were measured, with the results suggesting that the overall mechanical behaviour of the unit is determined by the clay matrix properties. The mineral composition of the less than two micron fraction of this material was determined by X-ray diffraction. The clay minerals present are illite and montmorillonite. The percentage of montmorillonite reaches the 10% of the matrix fraction and may exert great influence upon the Atterberg limits, swelling, water adsorption, and shrinkage of the matrix material. Montmorillonite absorbs water between its individual silicate layers with resulting high swelling and low frictional resistance becoming by itself a contributing factor to the failures. The presence of expandable clay minerals within the chaotic unit of the Pindos flysh, may indicate that the remove of loose soil cover from the slopes of the reservoir area during the construction of the dam, may be inadequate for preventing future landslides, and a sealing up process may be needed.